MANAGING JUST WORLD BELIEFS IN AN UNJUST WORLD FOR VICTIMS OF SEXUAL VIOLENCE - Grove, Lindsey Chatfield (2019)
The foundational expectations for good things to happen to good people, while bad things happen to bad people, is referred to as the belief in a just world (BJW) hypothesis (Lerner, 1980; 1966). The understanding is that BJW is a deep-rooted belief that when challenged with injustice, an individual implements strategies in order to protect this core belief from shattering (Lerner, 1980). BJW has long explained victim blaming (Hayes, Lorenz, & Bell, 2013; Jones & Aronson, 1973) and a positive relationship with psychological protection for injustice to self (L Bègue & Bastounis, 2003; Lerner & Simmons, 1966; Sutton & Douglas, 205). BJW is clinically used to support recovery for victims of trauma by helping to make sense of their core beliefs about themselves, others, and the world that were influenced by trauma. In Cognitive Processing Therapy (CPT) the aim is to develop a moderate BJW in hopes for lower self-blame and improved psychosocial functioning (Resick, Monson, & Chard, 2016). In some situations blaming the self has been seen as a possible protection factor for injustice for self, although self-blame for sexual violence is correlated with poorer psychological functioning (Peter-hagene & Ullman, 2015; C. M. Reich et al., 2015). The focus for this paper is to explore the role of managing BJW (i.e., self-blame) for victims when they experience the injustice of sexual violence as university students. The cognitive understanding of why me could offer a significant contribution to these developments and provide discussion about the injustice of sexual violence (Furnham, 2003). Participants were 115 university college cisgender women and non-binary students who have experienced sexual violence in the past year, since being at UM, or since turning 18 and completed an online cross-sectional survey. Analysis focused on the pattern of relationship between BJW with trauma symptoms and the conditional indirect effect (moderated-mediation) of BJW management factors within the relationship path of sexual violence, BJW, and trauma symptoms. Results found a linear relationship between BJW-self and trauma symptoms, which was consistent with the BJW literature. BJW-S was found to fully mediate the relationship between sexual violence and trauma symptoms. Self-blame and crime recognition did not moderate this mediated relationship, although there was a significant moderating effect between not disclosing the sexual violence and receiving negative social support for the non-mediated relationship between sexual violence and trauma symptoms. Strengths, limitations, and future directions are discussed